Vitrinite Reflectance Suppression of the Triassic Chang 7 Shale: A Case Study from the Nijiahe Outcrop in the Ordos Basin - Qin, Jie (International Journal of Natural Resources and Environmental Studies, 2025)
The maturity of the Chang 7 shale in the Niejiahe section of the Tongchuan area of the Ordos Basin was studied based on Rock–Eval parameters, vitrinite reflectance, sterane isomerisation parameters, and aromatic methylphenanthrene parameters. The reflectance of vitrinite is 0.55% - 0.64%, and the value of Tmax is from 429°C to 453°C, which indicate the Chang 7 shale from the Niejiahe section is in the immature-low mature stage. While the isomerization parameters of C29 steranes reflect the maturity interval from 0.7% to 0.8%, and the equivalent vitrinite reflectance calculated from the methyl phenanthrene ratio of Chang 7 shale is from 0.74% to 0.86%, both of which indicate the Chang 7 shale has reached the mature stage. These reflect the significant suppression of vitrinite reflectance in the Chang 7 shale. There is a significant negative correlation between the vitrinite reflectance and the content of chloroform asphalt “A” and HI, indicating that the suppression of vitrinite reflectance is influenced by the infection of bitumen on vitrinite and hydrogen-enriched vitrinite. Therefore, when evaluating the hydrocarbon generation potential of Chang 7 shale based on vitrinite reflectance, the suppression of vitrinite reflectance should be considered.